Contributions of tutoring to the development of academic writing in graduate education - Carlos Andrés Salazar Gaviria; José Vicente Abad Olaya (Universidad de Caldas, 2023)
Earning a master's or doctoral degree often requires writing scientific articles, a challenging task for graduate students. A review of existing literature on writing in higher education underscores the need to learn more about the strategies tutors use when teaching their tutees how to prepare their theses and academic articles. Objective: Explore the contribution of tutoring to the composition of academic articles as graduation requirements and thereby to the development of academic literacies among master's degree students. Methodology: Descriptive case study following the interpretive paradigm. This qualitative study was conducted in a master's degree program in education at a private university in Medellin, Colombia. The data were collected through semistructured interviews with three tutors, two students, and one graduate student. The content was analyzed by utilizing open and axial coding. Results: The study revealed three pivotal functions performed by tutors in fostering academic literacies during their support for article writing: adept management of the tutor-tutee relationship concerning co-authorship, skillful guidance in navigating interactions with external agents who regulate publication, and proactive promotion of the tutees' relationship with writing and research, thereby fostering the configuration of their identity as authors and researchers.